MIDWIFERY Effect of Dragon Fruit Juice to Increase HB Levels of Pregnant Women: Dragon Fruit Juice to increase HB Levels - Andriani, Fitri; Asshobbiha, Haniyah (Institute of Accounting Research and Novation (IARN), 2023)
Anemia is a body condition characterized by the results of hemoglobin (Hb) levels in the blood that are lower than normal. Hemoglobin functions to carry oxygen and deliver it to all tissue cells of the body. The effect of Dragon Fruit Juice on Hemoglobin Levels in Pregnant Women is known. This type of research is descriptive using the Management case study method. Midwifery consists of 7 steps of Varney, namely: Basic data collection, Basic data Interpretation, Potential diagnosis, immediate action, planning, thorough implementation of care, midwifery and evaluating Its Success. The subject of the study was Mrs. N. subjective data were obtained for pregnant women Mrs. N G: I P: O A:O at 25 weeks gestation, with anemia. The results of the study were known to have hemoglobin levels before the administration of dragon fruit juice 9.8 and standard Hb levels of >11. The average value of hemoglobin levels on the 6th day of dragon fruit juice administration was 11. There is an Effect of Dragon Fruit Juice on Increasing Hb Levels in Pregnant Women. Non-pharmacological treatment for increasing hemoglobin levels, one of which is by giving dragon fruit juice to pregnant women. In addition, it is necessary to take preventive measures through providing information about nutrition in pregnancy to increase the knowledge of pregnant women. So that every pregnant woman is healthy in undergoing her pregnancy and especially avoids anemia.